Karnataka Annual Plan 1979-80 Volume I Review of Planning and Proposals for the Annual Plan - Planning Commission (Planning Commission, 1979)
Karnataka's economy has registered one of the highest growth rates in the country and in recent years an annual growth rate of around 6 per cent has been maintained. Such a growth has further strengthened agricultural, industrial, infrastructural and institutional base in the State- With a stronger base which the State now possesses and with still unexploited and under-utilised material and human resources, the State is launching a more optimistic programme of development in the new Five Year Plan 1978-83 keeping in view not only the immediate goals and problems, but also a long run perspective.
Planning Department Government of Karnataka